Modelling,Simulation And Validation Of 9 DOF Vehicles Model For Automatic Steering System - Abdul Kadir, Faizul Akmar; Mohammad Nasir, Mohd Zakaria; Hudha , Khisbullah; Amir, Mohd Zubir (Trans Tech Publications, 2012)

(untitled)
Autonomous vehicle have recently arouse great interest and attention in the academic worldwide because of their great potential.As the new features for driver assistance and active safety systems are growing rapidly in vehicles,the simulation within a virtual environment has become a necessity.A vehicle model is required to represent the vehicle behaviour as close as real vehicle in simulation software.This paper presents 9 DOF vehicle models which consist of handling and Calspan tire model develop in MATLAB SIMULINK environment to study the vehicle behaviour for double lane change (DLC) and step steer input test.Those criteria will be compared with validated vehicle software namely CarsimEd to evaluated the performance of the vehicle model involving lateral acceleration,yaw angle and yaw rate from both output. Results show the 9 DOF vehicle closely follows the CarsimEd trends with acceptable error at both conditions.